Social vulnerability assessment of barangays located in flood-prone areas of the major watersheds in the island of Negros, Philippines - Carmona, Ana Rosa A.; Ella, Victor B. (2017)
Accessed online through this link: https://journals.upd.edu.ph/index.php/SURP/article/view/7909/6897
Keywords: Risk assessment; Flood risk; Watersheds